Consensus molecular subtype 4 (CMS4)-targeted therapy in primary colon cancer: A proof-of-concept study - Peters, Niek A.; Constantinides, Alexander; Ubink, Inge; van Kuik, Joyce; Bloemendal, Haiko J.; van Dodewaard, Joyce M.; Brink, Menno A.; Schwartz, Thijs P.; Lolkema, Martijn P.J.K.; Lacle, Miangela M.; Moons, Leon M.; Geesing, Joost; et al. (Frontiers in Oncology, 2022)
Background – Mesenchymal Consensus Molecular Subtype 4 (CMS4) colon cancer is associated with poor prognosis and therapy resistance. In this proof-of-concept study, we assessed whether a rationally chosen drug could mitigate the distinguishing molecular features of primary CMS4 colon cancer. Methods – In the ImPACCT trial, informed consent was obtained for molecular subtyping at initial diagnosis of colon cancer using a validated RT-qPCR CMS4-test on three biopsies per tumor (Phase-1, n=69 patients), and for neoadjuvant CMS4-targeting therapy with imatinib (Phase-2, n=5). Pre- and post-treatment tumor biopsies were analyzed by RNA-sequencing and immunohistochemistry. Imatinib-induced gene expression changes were associated with molecular subtypes and survival in an independent cohort of 3232 primary colon cancer. Results – The CMS4-test classified 52/172 biopsies as CMS4 (30%). Five patients consented to imatinib treatment prior to surgery, yielding 15 pre- and 15 post-treatment samples for molecular analysis. Imatinib treatment caused significant suppression of mesenchymal genes and upregulation of genes encoding epithelial junctions. The gene expression changes induced by imatinib were associated with improved survival and a shift from CMS4 to CMS2. Conclusion – Imatinib may have value as a CMS-switching drug in primary colon cancer and induces a gene expression program that is associated with improved survival.